Tirzepatide as a novel effective and safe strategy for treating obesity: a systematic review and meta-analysis of randomized controlled trials - Cai, Wenting; Zhang, Ruobin; Yao, Yao; Wu, Qiuhui; Zhang, Jinping (Frontiers in Public Health, 2024)
Objective To systematically evaluate the efficacy and safety of a new hypoglycemic drug, tirzepatide, for treating obesity based on indicators such as BMI, waist circumference, and body weight.Methods A search formula was written using search terms such as "tirzepatide", "overweight", and "obesity". A comprehensive search was conducted on databases such as PubMed, Cochrane Library, Embase, and Web of Science using a computer. Random controlled trial (RCT) literature was selected based on inclusion and exclusion criteria. After weight, tirzepatide showed a more significant reduction effect compared to the control group[MD=-5.65, 95% CI (-7.47, -3.82), P<0.001],[MD=-10.06, 95% CI (-12.86, -7.25), P<0.001], [MD=-10.63, 95% CI (-12.42, -8.84), P<0.001]. In comparison with placebo, tirzepatide had a prominent advantage in weight loss≥20% and≥25%[RR=30.43, 95% CI (19.56, 47.33), P<0.00001], [RR=37.25, 95% CI (26.03, 53.30), P<0.00001]. Subgroup analysis showed a dose-dependent therapeutic effect. In terms of safety, compared with the placebo and insulin groups, the incidence of gastrointestinal adverse reactions was markedly higher in the tirzepatide group, slightly higher to the GLP-1 RAs group. The hypoglycemic(<70mg/dL) risk of tirzepatide was slightly higher to that of placebo and GLP-1 RAs, but significantly lower than that of the insulin group[RR=0.46, 95% CI(0.36, 0.58), P＜0.001]. The incidence of other adverse events, including pancreatitis, cholecystitis, major adverse cardiovascular events-4, hypersensitivity reactions, and neoplasms did not show significant statistical differences compared to the control group (P>0.05).Conclusion Tirzepatide, as a weight loss drug, significantly reduces BMI,waist circumference and body weight while gastrointestinal adverse reactions need to be vigilant. Overall, its efficacy is significant and its safety is high.